Adaptive Formation Control for Waterjet USV With Input and Output Constraints Based on Bioinspired Neurodynamics - Duansong Wang; Mingyu Fu (IEEE Access, 2019)
A safety guaranteed formation control problem for waterjet unmanned surface vehicles (USV) under the consideration of unmodeled dynamics, environmental disturbances, input saturation, and output constraints is addressed in this paper. The leader-follower method and line-of-sight (LOS) strategy are employed to achieve the desired formation structure. Firstly, two tan-type barrier Lyapunov functions (BLF) are designed to limit the formation errors always within a predefined range to avoid collisions and keep communications, it can also relax the assumption of each USV's initial position to random. Besides, a bioinspired neurodynamics method is involved to avoid the appearance of the virtual velocity differential terms in the control law, which is different from the traditional dynamic surface method and makes it easier to implement in practice. Further, adaptive neural networks (NN) are used to approximate unmodeled dynamics and an auxiliary dynamics system is introduced to handle the input saturation. It is proved that the uniform ultimate boundedness of all signals in the control system can be achieved. Finally, simulation studies show the effectiveness of the proposed control law.